Renewable Water Harvesting by Amyloid Aerogels and Sun (Adv. Sustainable Syst. 1/2022). (19th January 2022) - Peydayesh, Mohammad; Greber, Tiara; Haechler, Iwan; Armanious, Antonius; Jia, Xiangze; Usuelli, Mattia; Bagnani, Massimo; Mezzenga, Raffaele
Abstract : Solar‐Based Water Purification The cover art representing article number 2100309 by Raffaele Mezzenga and co‐workers depicts an artist's view of black/white Janus aerogels floating over the surface of an imaginary lake surrounded by cows producing the milk proteins from which the aerogels are made. These aerogels can be used for solar‐based water purification, producing safe drinking water at virtually no cost and no energy, besides freely available, and unlimited solar energy.